Answer:
i=2, -12/9
Step-by-step explanation:
Step one: Using FOIL: (4+3i) (6-3i)--> 4*6+4*-3i+ 3i*6+ 3i*-3i
Step two: Simplify the new equation--> 24-12i+18i-9i²
Step three: Putting that into the quadratic equation--> -9i²+6i+24
Step four: Use the quadratic formula or the X-method (I'm going to use the X-method)
Step five a: Setting it up to use the X-method--> ax²+bx+c=0
Step five b: a=-9 b=6 c=14
Step six:
Step seven:
Step eight: i= -2, -12/9
Hope that helps! Let me know if you need anymore help!